Models of reliability for cutting tools - Dašić, Predrag (Strojniški vestnik, 2008)
Reliability of machining systems depends to a great extent on the reliability of cutting tool performance with the latter being the weak link due to wear. Soil processing systems have many in common with machining systems and a major problem related to use of tillage equipment is ploughshare wear, as it markedly affects tillage quality and agricultural production economy. In the present study a machining and a soil processing example will be given for the determination and modelling of the reliability function R(T)Č for turning of 20CrMo5 steel alloy using Cubic Boron Nitride (CBN) and mixed ceramic cutting tools, and in a tillage operation using a straight toothed harrow. In the machining case, through comparative analysis of theoretical distribution models, which fit closer the experimental data, the Gaussian model is selected to represent the reliability function for both tool materials considered. In the tillage example, by carrying out an optimization procedure based upon the reliability function R(T) of the tillage system, a particular tool tooth geometry was found that establishes the maximum tooth working time possible for a reliable performance.
Keywords: kmetijski stroji; obdelovalni sistemi; rezalna orodja; obraba; zanesljivost